Case study of Block 1, Highland Towers Condominium collapsed in Taman Hillview, Ulu Klang, Selangor, Malaysia on 11th December 1993 - Solahuddin, Azuwa; Fadzil, Mat Yahaya (Elsevier B.V., 2023)
Landslide has become the primary focus in slope engineering as the case increases. Most landslides are resulted from an unknown confluence, and most occur on slopes created by humanity. Highland Towers were built between 1976 and 1979, and its occupants were primarily first and middle-class people. There is a steep hill behind the three blocks. The main draws here are the natural scenery and panoramic vista of Kuala Lumpur. This case study investigates what factors led to Block 1, Highland Towers condominium’s collapse on 11th December 1993 at 1.35 p.m. using reliability analysis approaches and human fault impact factors. The Block 1 collapse is caused by an unstable pile foundation. The engineers incorrectly estimated the horizontal load design, causing surcharge loads to be created by the downhill forward movement when the rotating retrogressive slide happens. However, several precautions may be taken to protect the building structures from landslide. It is common knowledge that structural reliability analysis yields failure probabilities that are not considered for human faults. Inadequate drainage, collapse of retaining wall, and rail piling foundation are all plausible explanations for this landslide initiation. Thus, combining structural and human reliability analysis are recommended to mitigate landslide, including slope hazards.